The effect of cold arc Gas Metal Arc Welding (GMAW) heat input to the 304L stainless steel joint - Nor Aqilah Yuza (2020)
The Cold Arc welding is a modification from gas metal arc welding (GMAW) technology which resulted in narrow fabrication tolerances, enhanced the quality of the weld and improved the welding productivity. It is a processed that reduced the heat input which is gained by controlling the ‘short arc’ process or also known as short circuiting metal transfer mode. Heat input employed significance role in controlling the weld response and affected the weldment properties. It was responsible in controlling the factor for thermochemical occurrence that happen in weld pools, it makes way for the cooling to alter the chemistry of weld metal. Welding of thin sheet metal products is very susceptible to distortion and deformation, caused by the thermal expansion of the material due to the welding heat input. It is still a huge challenge today as the corrosion resistance and mechanical properties are being affected when there was change in the microstructural that occurs while welding and at the weld joint. Thus in this project, it focus on Cold Arc GMAW with the aim to investigate the effect of heat input of Cold Arc GMAW to the 304SS joint. Good well quality referred to minimum value of the weld width and maximum value of the penetration depth. The optimum value for the penetration depth and width of bead weld is found at welding voltage 20 V and welding speed 5 mm/s at sample 4. The maximum Ultimate Tensile Strength (UTS) is 546.701 MPa which is high heat input however due to the burn out the sample is rejected. Therefore, the best sample compare to other is the sample 4 with UTS of 477.606 MPa, heat input of 546.701 J/mms, welding speed of 5 mm/s and welding voltage of 20 V.